FUND MANAGEMENT: AN EXPLARATORY CASE STUDY OF MOSQUES IN SOUTH SULAWESI INDONESIA - Agusdiwana Suarni; Andi Jam’an; Rabiatul Adawiah (Green Publisher, 2023)
This paper identifies the mosques' source of funds, fund distribution, and parties responsible for managing the fund. The research used mixed methods, qualitative research and quantitative, which interviewed mosque administrators and Jema'ah and collected secondary data through in-depth interviews in 80 mosques in South Sulawesi, Indonesia. The findings of this study solidify the results of previous research, where it was found that the primary sources of mosques' funds were public charity contributions. The fund was also utilized optimally for the operations and physical development of the mosques. Financial recording of the Mosque is only done when cash comes in and out. Then cash in and out, and the total cash is delivered using the Mosque's Microphone. This paper recommends that the government should have regulations regarding the disclosure of financial statements and fund management, such as making an annual report on Mosques overseas, such as Masjid Taqwa Brisbane and Mosque foundation in the UK